Tuning visible-light absorption properties of Ru–diacetylide complexes: simple access to colorful efficient dyes for DSSCs1. Issue 35 (21st September 2015) - De Sousa, Samuel; Lyu, Siliu; Ducasse, Laurent; Toupance, Thierry; Olivier, Céline
<x xml:space="preserve">Abstract</x> An attractive color palette of red, violet and blue-green chromophores was prepared for dye-sensitized solar cell applications. The chromophores are used in single-dye and co-sensitized devices.